English Curriculum Analysis for Mental Retardation Students - M. Iqbal Liayong Pratama (Jadila: Journal of Development and Innovation in Language and Literature Education, 2024)
English language learning success is determined by many factors, such as the administration curriculum, which is used as lesson preparation, method, and evaluation of media used. as well as in SMPLBN Kepahiang, requiring a systematic analysis to analyze the curriculum to support learning success. This prompted the authors to conduct this research. This research aims to curriculum analysis for Mental Retardation Students in SMLBN Kepahiang. The researcher used a descriptive qualitative method. Observation, unstructured interviews, and documentation were used as the data collection technique. To enhance validity, the researcher used the triangulation method. The finding shows that formulation of learning objectives or indicators and determining the materials and props used cannot be guided by the applicable curriculum but depends on the student’s condition. The forms of evaluation used in the process of learning English are used as an evaluation tool in learning the English language is SMPLBN dikepahiang multiple choice questions by preparing the material as well as the activities carried out at the end of the semester; barriers to evaluating the election is a straightforward question with a vocabulary that students easily understand. Suppose the student is considered not finished, then performed remedial continuously. It is suggested that The Headmaster try to complement a variety of facilities and infrastructure required and improve teachers’ performance. English teachers try to improve the administrative requirements, ways of learning, and instructional media used.